THE IMPACT OF CENTRAL BANK DIGITAL CURRENCY (CBDC) VOLATILITY ON MONETARY POLICY EFFICIENCY IN FINANCIAL INCLUSION AND INVESTMENT - Pratiwi, Eva Novita (Journal of Social and Economics Research, 2024)
This paper explores the impact of Central Bank Digital Currency (CBDC) volatility on the efficiency of monetary policy, focusing on its role in financial inclusion and investment. As the world increasingly embraces digital currencies, central banks are exploring the potential benefits and risks associated with CBDCs. Volatility in CBDCs may have significant implications for the effectiveness of monetary policy, potentially influencing inflation control, interest rates, and economic stability. Moreover, CBDCs' introduction could either enhance or hinder financial inclusion by providing new opportunities for unbanked populations or exacerbating existing disparities. The paper reviews existing literature on CBDCs, highlighting key findings on their volatility and its effects on policy formulation. Furthermore, it assesses how volatility may impact investment decisions, both in terms of risk perception and market behavior. By examining the intersection of monetary policy, financial inclusion, and investment, this paper aims to provide a comprehensive understanding of CBDCs' potential in shaping modern economies. It is critical for policymakers to consider the dynamic nature of CBDC volatility when designing strategies for effective financial inclusion and sustainable investment. The paper concludes by identifying gaps in the current literature and proposing future research directions to further explore CBDC's impact on global economic systems. Ultimately, this review underscores the importance of mitigating volatility to maximize CBDCs' benefits in fostering inclusive economic growth.